Fifty years of Asian experience in the spread of education and healthcare - Sudipto Mundle (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper analyses the dramatic spread of education and healthcare in Asia and also the large variations in that spread across and within countries over 50 years. Apart from differences in initial conditions and income levels, the nature of the state has also been an important determinant of these variations. This is because social development has typically been led by the state. But in most countries, public resource constraints and the growing dependence on private provision and private spending have generated a pattern of nested disparities in the access to education and healthcare between rich and poor regions, between rural and urban areas within regions, and between rich and poor households within these areas. However, as the better-off regions, areas, and households approach the upper limits of achievable education and health standards, a process of convergence is also underway as those left behind begin to catch up.
Keywords: B25; H51; H52; I13; I18; I28; 330; Asia; comparative studies; disparity; education; health; state